Effects of Emerging Technologies on African Development: A Narrative Review on Selected African Countries - Kazeem Ajasa Badaru; Ramashego Shila Mphahlele (Research in Social Sciences and Technology- OpenED Network, 2023)
The rapid onset of the COVID-19 pandemic, also known as the SARS-CoV-2 outbreak, has brought to light how important technology may be to the socio-economic development of a nation, particularly in Africa. The study conducted a narrative review of pertinent literature to objectively assess the effects of two types of emerging digital technologies (Artificial Intelligence [AI]) and nanotechnologies in Africa. The results showed that emerging technology-related research, development, and deployment are happening throughout Africa. Nanotechnology and AI have had a substantial impact in many spheres of African economies. The study, however, acknowledges in its conclusion that not all African nations have derived the same benefits from emerging technologies, including the digitalisation processes. There are still large disparities in the accessibility of technology and digital skills in several rural and underdeveloped areas in Africa. Thus, recommendations on how to close these gaps are provided for all African countries to profit more consistently from the emerging technologies and the digitalisation processes.